Factors affecting proteasome dynamics and localization - Burris, Alicia (Kansas State University, 2020)
Proteasomes are essential, multisubunit complexes that control cellular processes and proteostasis by selectively degrading proteins. Their function depends on the coordination between two major subcomplexes, the regulatory particle (RP) and the core particle (CP). The CP forms a cylindrical structure that cleaves substrates but has closed gates on either end that limits substrate entry. The regulatory particle opens these gates, recognizes the substrates, and unfolds them into the core particle. Besides RP, other proteasome associated proteins, like Blm10, can open the gates and thereby activate the CP. Blm10 is a large, monomeric protein that binds to the same interface of CP as the regulatory particle; however, it remains poorly understood how the mutually exclusive binding between these activators is regulated. The work in this dissertation addresses this by studying Blm10 and Blm10-CP complexes including how their levels are regulated by various stress conditions, and how that affects the proteasome landscape. Our results show that upon overexpression of Blm10, all RP-CP complexes were replaced by Blm10-CP complexes. This indicates that Blm10, which is normally present at substoichiometric levels relative to CP, can compete with RP and change the proteasome landscape. The emergence of almost exclusively Blm10-CP complexes compromised the proteasome’s ability to degrade substrates as indicated by an accumulation of ubiquitinated material. However, under stress conditions, like prolonged cell growth, Blm10 and Blm10-CP complexes were targeted for autophagy and vacuolar degradation, while RP-CP complexes were not. Consistent with this difference in fate between complexes, we saw no colocalization of Blm10 and CP in proteasome storage granules (PSGs) following glucose starvation while RP and CP are found in the same granules. This was surprising as previous work indicated a role for Blm10 in PSG formation. As PSGs require proteasome export from the nucleus we also focused on other factors involved in this process. Interestingly, proteasomes fail to be exported from the nucleus in cells containing a mutant form of Rpn11, a lid subunit of the regulatory particle. This mutant, rpn11-m1, has a frameshift mutation resulting in the loss of its terminal alpha helix. Therefore, we created a new mutant, Rpn11-∆31, which produced a clean truncation. This mutant prevented the proteasome from localizing to PSGs and showed severe growth defects, indicating we could use this mutant to study proteasome nuclear export. Our results showed that truncating Rpn11 affected incorporation of late stage lid subunits Rpn7 and Rpn12 which themselves contain putative nuclear export signals for the common export protein Crm1. However, further analysis indicated that Crm1 was not involved in export of the proteasome under glucose starvation. Nevertheless, unincorporated Rpn7 and Rpn12 did accumulate in granule-like structures while the remainder of the proteasome remained nuclear. This suggests that unincorporated lid subunits might be stored in granule-like structures until they can be successfully incorporated into the proteasome. In sum, this thesis provides a better understanding of the dynamics of proteasome complexes and how changing these dynamics affects proteasome localization and function.
Keywords: Proteasome; Blm10; Rpn11; Assembly; Autophagy